Time, income and subjective well-being - Interdependent multidimensional polarization: 20 Years in Germany - Joachim Merz; Bettina Scherg (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2022)
Society drifts apart in many dimensions. Economists focus on income of the poor and rich and the distribution of income, however a broader spectrum of dimensions is required to draw the picture of multiple facets of individual life. In our study of multidimensional polarization we extend the income dimension by time, a pre-requisite and fundamental resource of any individual activity. We consider genuine personal leisure time as a pronounced source of social participation in the sense of social inclusion/exclusion and Amartya Sen's capability approach. With an interdependence approach to multidimensional (IMD) polarization compensation between time and income, parameters of a CES-type subjective well-being function, is evaluated empirically by the German population and based on German Socio-Economic Panel (GSOEP) and detailed time use diary data from the three German Time Use Surveys (GTUS) 1991/92, 2001/02 and the actual 2012/13. The focus is on the working poor and rich self-employed and employees. The background of IMD polarization incidence (risk) and intensity (magnitude) is estimated by a two-stage selectivity controlling approach. Main result: Time, additional to income, is a significant subjective well-being and polarization dimension. Its interdependence/compensation is of economic and statistical significance. Over 20 years IMD Polarization-incidence (risk) is about 20% (self-employed getting poorer compared to employees). Polarization-intensity (magnitude), however, increased significantly by 22% (stronger polarization of the self-employed), a distinct polarization drift to the tail ends of the distribution of time and income. – – Die Gesellschaft driftet in vielen Dimensionen auseinander. Ökonomen fokussieren auf Arme und Reiche und die Verteilung des Einkommens. Allerdings ist ein breiteres Spektrum erforderlich, um das Bild der vielfältigen Facetten des individuellen Lebens zu zeichnen. In unserer Studie multidimensionaler Polarisierung erweitern wir die Einkommens- um die Zeitdimension, eine Grundvoraussetzung und fundamentale Ressource jeder individuellen Aktivität. Im Besonderen betrachten wir die genuine persönliche freie Zeit als eine hervorzuhebende Quelle sozialer Partizipation im Sinne einer Inklusion/Exklusion und Amartya Sen's Verwirklichungschancen (capability approach). Mit einem interdependenten multidimensionalen (IMD) Polarisierungsansatz erlauben wir eine Kompensation zwischen Zeit und Einkommen, Parameter einer CES-Typ Zufriedenheitsfunktion, empirisch bewertet von der deutschen Bevölkerung auf der Basis des Sozio-oekonomischen Panels (GSOEP) und detaillierte Zeitverwendungstagebuchdaten der drei deutschen Zeitverwendungsstudien (GTUS) 1991/92, 2001/02 und aktuell 2012/13. Der Fokus richtet sich auf arme (working poor) und reiche Selbständige und abhängig Erwerbstätige. Der Hintergrund von IMD Inzidenz (Risiko) und IMD Intensität (Ausmaß) wird mit einem zweistufigen selektionskorrigierenden Ansatz geschätzt. Hauptergebnis: Zeit, ergänzend zum Einkommen, ist eine signifikante Zufriedenheits- und Polarisierungsdimension. Seine Interdependenz/Kompensation ist von ökonomischer und statistischer Signifikanz. Über 20 Jahre liegt die Polarisierungs-Inzidenz (Risiko) bei 20% (mehr ärmer werdende Selbständige). Jedoch, es steigt die Polarisierungs-Intensität (Ausmaß) signifikant um 22% (stärkere Polarisierung bei den Selbständigen), eine ausgeprägte Polari-sierungstendenz zu den Verteilungsenden von Zeit und Einkommen,
Keywords: I32; D31; J22; 330; Interdependente multidimensionale Polarisierung; genuine persönliche Freizeit; Einkommen; arme und reiche Erwerbstätige (working poor); Zufriedenheit; minimale multidimensionale Polarisierungsintensitätslücke (2DGAP); Soziale Partizipation; zweistufige Heckman-Schätzungen der Polarisierungsinzidenz (Risiko) und -intensität (Ausmaß); Deutsches Sozio-oekonomisches Panel (SOEP); Deutsche Zeitbudgetstudien 1991/92; 2001/02 and 2012/13; Interdependent multidimensional polarization; genuine personal leisure time; income; working poor and affluent; subjective well-being; minimum multidimensional polarization intensity gap (2DGAP); social participation; two-stage Heckman estimates of polarization incidence (risk) and intensity (magnitude); German Socio-Economic Panel (SOEP); German Time Use Surveys 1991/92; 2001/02 and 2012/13